Assisting MSMEs in Preparing Integrated Financial Reports with Tax Reporting - Permatasari, Maulina Dyah; Yulianti, Vista; Wulandari, Dian Sulistyorini; Hasanah, Yunisa Amardhea (PT FORMOSA CENDEKIA GLOBAL, 2024)
This community service program, aimed to enhance the financial literacy and tax compliance of Micro, Small, and Medium Enterprises (MSMEs). Conducted from October 7 to October 21, 2024, the program involved 10 MSME participants and was held at one of the participant’s business locations. The initiative addressed the common challenges MSMEs face in financial reporting and compliance with tax regulations through a structured series of workshops, hands-on training, and mentoring sessions. The program’s activities included introductory sessions on financial reporting basics, tax compliance regulations, and integration with affordable digital accounting tools. Participants were guided in preparing financial statements and tax reports under close supervision. The results showed a significant improvement in participants' abilities, with 90% successfully preparing financial reports, 90% demonstrating an understanding of tax compliance, and 80% adopting digital tools—an increase from 30%, 40%, and 10%, respectively, before the program. The findings highlight the program's effectiveness in equipping MSMEs with practical skills for better financial management and regulatory compliance.